Electron paramagnetic resonance studies of bulk Mg‐doped GaN grown by high nitrogen pressure solution method. Issue 4 (18th March 2015) - Dashdorj, J.; Willoughby, W. R.; Zvanut, M. E.; Bockowski, M.
Abstract: An acceptor‐related impurity was studied in bulk free standing GaN using electron paramagnetic resonance spectroscopy. Both undoped and Mg‐doped substrates grown by the high nitrogen pressure solution method were examined, but only the doped sample revealed the presence of an EPR‐detected center. Comparison with earlier work on p ‐type GaN films suggests that the defect is an acceptor, heavily compensated during growth. Photo‐EPR studies revealed a photo‐ionization threshold of 2.8 eV, which is interpreted as excitation of an electron from the acceptor to the conduction band. Based on the concentration and photo‐threshold, the EPR center detected in the HNPS doped samples is tentatively identified as Be, which SIMS measurements indicate is a trace impurity in the doped GaN sample. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)